2019
DOI: 10.1038/s41598-019-55935-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Capability of an Ecosystem Nature-Restoration in Coal Mined Area

Abstract: Ecosystem issues have been severely concerned and studied when the coal resource is one of major energy generators, and green mining innovation techniques involving artificial-restorations have addressed and significantly lessened negative impacts on the ecological environment. The ecosystem of a coal-mined area, however, is able to naturally restore with the processes of natural succession, similar to the human body system that has the immune ability to self-heal a wound over time if the wound does not deeply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Many dams and major river systems occur in the coal-mining regions of South Africa and mining activities pose a serious pollution threat to these national watercourses and thus provision of potable water [40]. Although coal dumps and overburden (also called spoil) are known to self-rehabilitate without human intervention, this depends on a number of factors and can take decades to effectively minimize or negate any deleterious environmental impact [43]. Often, because of high temperatures, spontaneous combustion occurs, and a high clay content, poor substrate porosity and aeration, waterlogging, and a heteromorphous structure can combine to make it difficult for cover vegetation to succeed [38,[44][45][46].…”
Section: Impact Of Mining-induced Land Disturbance and Appropriate Stewardshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Many dams and major river systems occur in the coal-mining regions of South Africa and mining activities pose a serious pollution threat to these national watercourses and thus provision of potable water [40]. Although coal dumps and overburden (also called spoil) are known to self-rehabilitate without human intervention, this depends on a number of factors and can take decades to effectively minimize or negate any deleterious environmental impact [43]. Often, because of high temperatures, spontaneous combustion occurs, and a high clay content, poor substrate porosity and aeration, waterlogging, and a heteromorphous structure can combine to make it difficult for cover vegetation to succeed [38,[44][45][46].…”
Section: Impact Of Mining-induced Land Disturbance and Appropriate Stewardshipmentioning
confidence: 99%
“…At the same time, newly restored land must allow for different land-use opportunities, mitigate against environmental deterioration, and resemble the surrounding landscape which may be very different from its historical state. While land disturbed by mining can apparently "quickly restore itself" naturally [43], whether such natural rehabilitation processes repair and re-invigorate land for viable post-mining agriculture or forestry is largely unknown or at best, poorly documented. A retrospective account of the key priorities in the rehabilitation of mined land in Australia recognized that emergence of open cast mining had increased the footprint of the environmental disturbance, which in turn accelerated the evolution in rehabilitation priorities of that country [50].…”
Section: Impact Of Mining-induced Land Disturbance and Appropriate Stewardshipmentioning
confidence: 99%
“…The reason is that the goaf, as time goes by, has basically collapsed after the coal seam is mined, and gradually compacted during the main roof rotation and subsidence process. The surrounding rock tends to be stable, and the surface SWC shows "self-recovery" [53] feature. The measuring points from No.…”
Section: Variation In Shallow Swc Before and After Miningmentioning
confidence: 99%
“…Li et al (2020) have reported that phytoremediation continuously increases soil nutrients and ecological stability. Vegetation restoration using certain woody species and vegetation can facilitate soil self‐sustainment by rectifying nutrient levels and by facilitating the accumulation of nutrients to achieve sustainable development of the degraded land (Cui et al, 2019; Dowarah et al, 2009). Studies have shown that comprehensive land suitability analysis and ecosystem service evaluation can be used to aid selection of the best land restoration method (Soltanmohammadi et al, 2010; Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%